Failure and Ejection Behavior of Concrete Materials under Internal Blast - Haifu Wang; Jianguang Xiao; Yuanfeng Zheng; Qingbo Yu (Shock and Vibration)
In order to investigate the failure and ejection behavior of concrete materials under internal blast, the default Riedel-Hiermaier-Thoma (RHT) concrete model in AUTODYN and a meshfree processor called SPH are employed in this numerical simulation. It is shown that the failure mechanisms are significantly different in these damaged zones. Crushed zone is caused by shear failure while fractured zone is induced by tensile failure, and spalled zone is formed by a combination of shear and tensile failure. In addition, the ejection velocity distribution of the fragmented concrete mass on free surface is examined. The results indicate that the ejection velocity declines monotonously with the increase of the distance to symmetry axis of computational model. On the wall of the prefabricated borehole, two types of fragmented concrete mass are analyzed, and bottom initiation is recommended to eject the fragmented concrete mass effectively. Moreover, an algorithm of average ejection speed is developed to effectively estimate the drill capacity of high velocity, energetic (HE) projectiles. At last, the validity of numerical simulation is verified by physical experiments.